2011
DOI: 10.1007/s00417-010-1598-0
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of selenite toxicity and cataractogenesis in cultured rat lenses by Vitex negundo

Abstract: These results suggest that FVN treatment prevented selenite toxicity and cataractogenesis by maintaining antioxidant status, calcium homeostasis, protecting sulfhydryl group, and decreasing oxidative stress in lens, which may be due to its protective effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Calcium concentrations in the lens samples were analyzed flame photometrically with standard prepared from CaCO 3 and deionized water. The results were expressed as μmoles/g wet tissue (21).…”
Section: Methodsmentioning
confidence: 99%
“…Calcium concentrations in the lens samples were analyzed flame photometrically with standard prepared from CaCO 3 and deionized water. The results were expressed as μmoles/g wet tissue (21).…”
Section: Methodsmentioning
confidence: 99%
“…The glucoside of isorhamnetin (methylated quercetin), isolated as a bioactive flavonoid from the leaves of Cochlospermum religiosum (Gayathri et al ., 2010 ) and flavonoid fraction isolated from fresh leaves of Vitex negundo (Rooban et al ., 2011 ) protected enucleated rat eye lenses against selenite-induced cataract in an in vitro culture model.…”
Section: Anticataract Action Of Flavonoidsmentioning
confidence: 99%
“…Ocimum sanctum (Lamiaceae) Extract of plant inhibition of polyol accumulation (Halder et al, 2003) Origanum vulgare Extract of plant Inhibit the oxidative damage and reduces the lipid peroxidation. (Dailami et al, 2010) Pterocarpus marsupium (Fabaceae) aqueous extract Inhibits the diabetes induced cataract (Vats et al, 2004) Silybum marianum (Compositae) seeds extract Inhibit the oxidative damage (Huseini et al,2004) Trigonella foenum graceum (Fabaceae) Seed extract Inhibit the generated oxidative stress (Lija et al, 2006) Vitex negundo (verbanaceae) flavonoids fraction Inhibits the oxidative stress (Rooban et al, 2011) Withania somnifera (solanaceae) Extract of plant Inhibits the oxidative stress (Thiagarajan et al, 2003) PLANT PRODUCTS AGAINST CATARACTS reactive oxygen species, which causes the lipid peroxidations and thus play major role in development of diabetic secondary complications in kidney, blood vessels, eye and nerve . The natural antioxidant such as ascorbic acid, vitamin E, and carotinoids have been screened and it was found that antioxidant has protective action against cataract.…”
Section: Plant Products Against Cataractsmentioning
confidence: 99%